Duration of Follow-up and Timing of Discharge from Imaging Follow-up, in Adult Patients with Urolithiasis After Surgical or Medical Intervention: A Systematic Review and Meta-analysis from the European Association of Urology Guideline Panel on Urolithiasis - Tzelves, Lazaros; Geraghty, Robert; Lombardo, Riccardo; Davis, Niall F; Petřík, Ales; Neisius, Andreas; Gambaro, Giovanni; Türk, Christian; Thomas, Kay; Somani, Bhaskar; Skolarikos, Andreas (European urology focus, 2023)
CONTEXT: No algorithm exists for structured follow-up of urolithiasis patients. OBJECTIVE: To provide a discharge time point during follow-up of urolithiasis patients after treatment. EVIDENCE ACQUISITION: We performed a systematic review of PubMed/Medline, EMBASE, Cochrane Library, clinicaltrials.gov, and reference lists according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Fifty studies were eligible. EVIDENCE SYNTHESIS: From a pooled analysis of 5467 stone-free patients, we estimated that for a safety margin of 80% for remaining stone free, patients should be followed up using imaging, for at least 2 yr (radiopaque stones) or 3 yr (radiolucent stones) before being discharged. Patients should be discharged after 5 yr of no recurrence with a safety margin of 90%. Regarding residual disease, patients with fragments ≤4 mm could be offered surveillance up to 4 yr since intervention rates range between 17% and 29%, disease progression between 9% and 34%, and spontaneous passage between 21% and 34% at 49 mo. Patients with larger residual fragments should be offered further definitive intervention since intervention rates are high (24-100%). Insufficient data exist for high-risk patients, but the current literature dictates that patients who are adherent to targeted medical treatment seem to experience less stone growth or regrowth of residual fragments, and may be discharged after 36-48 mo of nonprogressive disease on imaging. CONCLUSIONS: This systematic review and meta-analysis indicates that stone-free patients with radiopaque or radiolucent stones should be followed up to 2 or 3 yr, respectively. In patients with residual fragments ≤4 mm, surveillance or intervention can be advised according to patient preferences and characteristics, while for those with larger residual fragments, reintervention should be scheduled. PATIENT SUMMARY: Here, we review the literature regarding follow-up of urolithiasis patients. Patients who have no stones after treatment should be seen up to 2-3 yr, those with large fragments should be reoperated, and those with small fragments could be offered surveillance with imaging.
Keywords: Urology; Urolithiasis; Discharge; následné studie; litotripse; Adult; dospělí; urolitiáza; Metabolic; Follow-Up Studies; Urinary stone treatment; Follow-up; lidé; Humans; Patient Discharge; propuštění pacienta; Imaging; Lithotripsy; urologie